Ethics and Accountability in Government Bureaucracy - Ousu Mendy (Fakultas Hukum Universitas Lampung, 2023)
For the past few years, a contentious issue of accountability among government bureaucrats has remained as topical as it is relevant to governance. This research brings in an exposition of the role of ethics in ensuring accountability among government bureaucrats as animated by transparency. To realize this, a normative research method is used through secondary data. Relevant literature like books and journals are sufficiently used to paint out the existing and prevailing circumstances in government bureaucracy. Accountability is one of the tools in controlling ethical conduct of government bureaucrats. There are instances of purported power abuse made in public service, showing government bureaucracy’s disregard for ethical standards. The question of whether the state, as sovereign, should be held accountable to anyone or viewed as a moral and responsible agent has been well debated in political science literature going all the way back to Hobbes’ time. Accountability is achievable by presenting multiple and dynamic accountability obligations to administrators and low-level bureaucrats. An institutional approach questions principal-agent assumptions regarding what accountability entails, how it is demanded, rendered, evaluated, and assigned, as well as how accountable institutions function and change.